A Website Content Analysis on Corporate Social Responsibility Disclosures in Baltic Sea Shipping - Kunnaala-Hyrkki, Vappu; Brunila, Olli-Pekka; Inkinen, Tommi (Springer Nature, 2026)
In the past decades, there has been a significant increase in the emphasis on sustainability across industries. Correspondingly, the shipping industry is increasingly focusing on sustainability and corporate social responsibility (CSR), by integrating environmental, social, and economic concerns into their strategies and operations. Shipping companies actively pursue responsible practices to align with stakeholder expectations. By doing so, they can strengthen stakeholder trust, enhance their corporate reputation and ensure operational legitimacy. Clear and consistent communication with stakeholders is integral to the success of CSR initiatives, as it not only raises awareness of the company’s efforts but also invites valuable feedback. Without effective stakeholder communication, companies may miss out on the full benefits of CSR. An increasing number of shipping companies are providing stakeholders with CSR disclosures. This paper investigates how shipping companies located in the Baltic Sea region communicate their CSR disclosures on their websites. This study consists of a website content analysis of the ten largest shipping companies by fleet size in each Baltic Sea country, focusing on how prominently they present CSR-related content. The findings reveal that shipping companies do provide CSR disclosures on their websites, but the scope and content of the disclosures varies, with environmental aspects most often at the core. The differences between larger shipping companies and other companies examined were not significant as even some of the largest companies did not address sustainability on their websites.